STUDI KELAYAKAN, PERENCANAAN, DETAIL DESAIN DAN DESAIN SISTEM MODEL PLTMH PADA BAK PELEPAS TEKAN (BPT) PDAM KABUPATEN GUNUNGKIDUL - , MASRUR ALATAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Gunungkidul is mountainous and drought-prone areas. These conditions cause some areas had difficulties of water supply . As the main body needs to perform metabolism and maintain a healthy body the water intake must be sufficient. PDAM as the water service provider for the community requires a technology that can produce energy, so that the water from low-lying areas can be lifted to higher areas. In the development of Micro Hydro Power Electric (Pembangkit Listrik Tenaga Mikro Hidro /PLTMH ) is not only meet the needs of electrical and lighting. The system can be part of a clean water system supplier for the community. This study was aimed to conduct a feasibility study, planning, design and manufacturing of installation system of laboratory testing. The results of this study are expected to produce method as an effort to raise water from the lower to the higher area. The study started with the collection of secondary data and primary data through surveys, discharge (Q) measurements, the potential Head (H) measurements, Feasibility Study, planning, turbine design manufacturing and civil buildings design. Turbines used in the study was cross flow turbine with blade number of 24 pieces, in earlier tests with the Head of 2.9 m produces the characteristics of Q = 40 Vs, Pout = 593.94 watts , N = 1273 rpm and rl = 96 % . Testing laboratory model system using the penstock installation of 4 inches PVC pipe, and Head of 4 m , with a working pump system or Pump As Turbine ( PAT ), resulted in the characteristics of Q in = 20 1/s , N turbine of 646 rpm and rl = 98.9% and was able to lift water up to 7.5 m.